HUBUNGAN KOMUNIKASI INTERPERSONAL KEPALA SEKOLAH DENGAN KINERJA GURU JURUSAN OTKP SMK SWASTA DI KOTA CIMAHI - Necha Clorenza Br Pinem, - (2021)
This research aims to determine the relationship between the principal's interpersonal communication and the performance of teachers in the OTKP Department of Private Vocational Schools in Cimahi City. The research was conducted using an explanatory survey method. The data collection technique used is a 4-scale Likert scale questionnaire. The population used were teachers of the OTKP Department of Private Vocational Schools in Cimahi City, namely SMK PGRI 1 Cimahi, SMK PGRI 2 Cimahi, and SMK Pasundan 3 Cimahi totaling 66 teachers. The data analysis technique used is the Spearman Rank correlation analysis technique. The results showed that there was a low relationship with a positive direction between the principal 's interpersonal communication and teacher performance . Thus, it can be concluded that the teacher's performance will increase if the principal's interpersonal communication is high, and vice versa, the teacher's performance will decrease if the principal's interpersonal communication is low.